2001
DOI: 10.1111/j.1745-4514.2001.tb00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Vitamin E Inhibits Poultry Pse and Improves Meat Functional Properties

Abstract: The objective of this work was to investigate the occurrence of pale, soft, exudative meat (PSE) in chicken by submitting birds to physical stress. Dietary supplementation of vitamin E was undertaken to overcome this syndrome. Postmortem muscle biochemical events and their consequence on meat properties were evaluated in samples with and without supplemented vitamin E. Our studies showed chickens were susceptible to heat stress which promoted changes in the glycolytic parameters causing the development of chic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
103
1
18

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(135 citation statements)
references
References 25 publications
13
103
1
18
Order By: Relevance
“…This effect is primarily due to the incorporation of the vitamin E into the subcellular membranes, where it maximises the antioxidant capacity (Monahan, et al, 1994;Buckley et al, 1995). It is also believed to suppress the development of Pale, Soft and Exudative (PSE) in chicken breast meat thus improving meat functional properties (Olivo et al, 2001). The objective of this work was to evaluate the antioxidative activities role of dietary vitamin E on WOF breast chicken meat and by exogenously application.…”
Section: Introductionmentioning
confidence: 99%
“…This effect is primarily due to the incorporation of the vitamin E into the subcellular membranes, where it maximises the antioxidant capacity (Monahan, et al, 1994;Buckley et al, 1995). It is also believed to suppress the development of Pale, Soft and Exudative (PSE) in chicken breast meat thus improving meat functional properties (Olivo et al, 2001). The objective of this work was to evaluate the antioxidative activities role of dietary vitamin E on WOF breast chicken meat and by exogenously application.…”
Section: Introductionmentioning
confidence: 99%
“…The L* and a* values found were lower and the b* values were higher than those found in dry and cured loins (ALIÑO et al, 2009). The ratio a*/b* can be used to verify the relationship between oxymyoglobin and metmyoglobin (OLIVO et al, 2001). In the present study, it was observed a decrease in the ratio a*/b* with an increase in the sodium chloride levels in the pork meat samples, indicating the formation of metmyoglobin submitted to different sodium chloride (NaCl) levels are shown in Table 1.…”
Section: Resultsmentioning
confidence: 55%
“…Analysis was performed in triplicate at 24 h postmortem as previously described by Olivo et al (2001). A colorimeter (Konica Minolta CR400) was used to evaluate the color parameters, including L* (lightness), a* (redness) and b* (yellowness), on the posterior surface of the intact skinless breast muscles at 24 h postmortem.…”
Section: Ph and Color Measurementmentioning
confidence: 99%
“…This rapid postmortem glycolysis with low pH values and high carcass temperature promote the denaturation of myofibrillar and sarcoplasmic proteins, thus compromising their functional properties and making them inappropriate for processing characterizing the so-called PSE meat (Olivo et al 2001;Kissel et al 2009). Thus, it is feasible to measure the stressful conditions intensity the animals are submitted by determining quantitatively the incidence of PSE meat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation